Comparison of Farmer Welfare in Kediri Regency and Probolinggo Regency Based on Farmer Exchange Rates (FER) - Prayitno, Gunawan; Anwar, Ruslin; Indrayanto, Toni; Permana, Mirza; Purnomowati, Rahmi (Journal of Regional and Rural Studies, 2024)
Agriculture is an important component of the Indonesian economy and makes a significant contribution to national Gross Domestic Product (GDP). However, the poverty rate among farmers is still high, which shows the need for a more in-depth study of farmer welfare. This study focuses on Kediri Regency and Probolinggo Regency in East Java, areas known for their agricultural contributions. The aim is to assess the welfare of farmers in Kediri Regency and Probolinggo Regency. This research uses a quantitative approach, with data collected through questionnaires and interviews. The analysis used is the Farmer Exchange Rate (FER), which is determined by comparing the Price Index Received by Farmers (It) and the Price Index Paid by Farmers (Ib). The results show significant differences between the two districts, Kediri experienced an increase in FER of 0.48%, while Probolinggo experienced a decrease in FER of 2.87%. This finding is important because it reflects differences in the welfare and economic conditions of farmers in Kediri and Probolinggo. Factors such as government support, adoption of modern technology, and seasonal changes were identified as influencing these outcomes. Strategic recommendations include increasing productivity through technology and starting programs targeting young farmers. This effort aims to improve agricultural effectiveness and the overall welfare of farmers in the region.